Neoarchaean subduction tectonics in Western Shandong Province, China: Evidence from geochemistry and zircon U–Pb–Hf isotopes of metabasalts. (11th August 2019) - Yang, Lihui; Hou, Guiting; Gao, Lei; Liu, Shuwen
Abstract : Neoarchaean supracrustal rocks, which were discovered in the Longhuzhai and Menglianggu areas of the Western Shandong Province (WSP) in the Eastern Block of the North China Craton (NCC), are fine‐ to medium‐grained amphibolites that commonly underwent greenschist‐ to amphibolite‐facies metamorphism. LA‐ICP‐MS zircon U–Pb analyses revealed that these metabasalts erupted at 2, 527 ± 5 to 2, 514 ± 4 Ma. These supracrustal rocks are tholeiitic basalts in chemical composition and exhibit relatively high SiO2 (49.30–53.34 wt%) and MgO (5.24–11.82 wt%) contents but low TiO2 (0.41–0.75 wt%) contents. They display flat chondrite‐normalized rare earth element (REE) patterns ((La/Yb)N  = 1.21–2.60) and negative Nb, Ta, and Ti anomalies ((Nb/La)PM  = 0.16–0.54), which are similar to those of typical island arc tholeiites (IATs) in subduction‐related settings. These findings, combined with the positive zircon εHf(t) values (+2.51 to +8.90) and εNd(t) values (+0.19 to +3.65), suggest that these metabasalts were derived from the partial melting of a depleted mantle source that was metasomatized by slab‐derived fluids at shallow levels in the upper mantle. Accordingly, the development of arc‐related tholeiitic volcanic rocks within the interior of the WSP imply that the Neoarchaean (2.6–2.5 Ga) subduction‐related slab–wedge interaction mechanism was widespread in the WSP and played a crucial role in the formation of the continental crust and its growth.